Hubungan Perceived Organizational Support dengan Work Engagement pada PNS Balai Besar POM di Medan - Ingrid Theodora Sitorus; Nenny Ika Putri Simarmata (Universitas Palan, 2026)
Work engagement is a crucial factor that supports organizational effectiveness, particularly within public institutions that bear significant responsibilities in delivering public services. This study aimed to examine the relationship between Perceived Organizational Support (POS) and Work Engagement among Civil Servants (Pegawai Negeri Sipil PNS) at the Medan Center for Drug and Food Control (Balai Besar Pengawas Obat dan Makanan BBPOM). A quantitative approach with a correlational research design was employed. The study population consisted of 127 civil servants, all of whom were included as research participants using a total sampling technique. Data were collected using the Survey of Perceived Organizational Support (SPOS) and the Utrecht Work Engagement Scale (UWES). Data analysis was conducted using the Pearson Product-Moment Correlation test. The findings revealed a positive and significant relationship between Perceived Organizational Support and Work Engagement (r = 0.266; p = 0.002). These results indicate that higher levels of perceived organizational support are associated with higher levels of employee work engagement. Descriptively, the majority of respondents reported high levels of POS (66.9%) and high levels of work engagement (73.2%). The findings suggest that organizational support manifested through fairness, concern for employee well-being, supervisory support, and recognition of employee contributions plays an important role in enhancing employees’ vigor, dedication, and involvement in their work. This study provides practical implications for BBPOM Medan to continuously strengthen organizational support as a strategic effort to improve employee work engagement and optimize the performance of civil servants.